2015
DOI: 10.1111/cbdd.12654
|View full text |Cite
|
Sign up to set email alerts
|

Novel Scaffold Identification of mGlu1 Receptor Negative Allosteric Modulators Using a Hierarchical Virtual Screening Approach

Abstract: Metabotropic glutamate receptor 1 (mGluR1) is considered as an attractive drug target for neuropathic pain treatments. The hierarchical virtual screening approach for identifying novel scaffolds of mGluR1 allosteric modulators was performed using a homology model built with the dopamine D3 crystal structure as template. The mGluR1 mutagenesis data, conserved amino acid sequences across class A and class C GPCRs, and previously reported multiple sequence alignments of class C GPCRs to the rhodopsin template, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…Virtual screening can be also used to identify allosteric modulators of GPCRs as it was done for muscarinic receptors [ 112 ] and metabotropic glutamate receptors [ 113 ]. Other successful examples of structure-based discovery of GPCR allosteric ligand include identification of GPR68 modulators by Huang et al [ 114 ], and muscarinic M 2 receptor modulators by Miao et al [ 112 ].…”
Section: High-throughput Docking As a Methods Of Virtual Screeningmentioning
confidence: 99%
“…Virtual screening can be also used to identify allosteric modulators of GPCRs as it was done for muscarinic receptors [ 112 ] and metabotropic glutamate receptors [ 113 ]. Other successful examples of structure-based discovery of GPCR allosteric ligand include identification of GPR68 modulators by Huang et al [ 114 ], and muscarinic M 2 receptor modulators by Miao et al [ 112 ].…”
Section: High-throughput Docking As a Methods Of Virtual Screeningmentioning
confidence: 99%
“…It has been shown that it is possible for homology models of GPCRs to identify potential ligands . There have been a number of studies aiming to evaluate the performance of homology models of GPCRs for in‐silico drug screening . For example, Tang et al studied beta‐2 adrenoreceptor (ADRB2) and showed that some homology models could exceed crystal structures in ligand virtual screening .…”
Section: Introductionmentioning
confidence: 99%
“…14 There have been a number of studies aiming to evaluate the performance of homology models of GPCRs for in-silico drug screening. [14][15][16][17][18][19][20][21] For example, Tang et al studied beta-2 adrenoreceptor (ADRB2) and showed that some homology models could exceed crystal structures in ligand virtual screening. 22 However, all of them only focus on 1 or a few GPCRs and their homology models, which do not provide a complete picture about the capability of homology model based methods for virtual screening of GPCR ligands.…”
mentioning
confidence: 99%
“…It has been shown that it is possible for homology models of GPCRs to identify potential ligands 14 . There have been a number of studies aiming to evaluate the performance of homology models of GPCRs for in-silico drug screening [14][15][16][17][18][19][20][21] . For example, Tang et al studied beta-2 adrenoreceptor (ADRB2) and showed that some homology models could exceed crystal structures in ligand virtual screening 22 .…”
Section: Introductionmentioning
confidence: 99%